A new procedure for recycling waste tailings as cemented paste backfill to underground stopes and open pits. (1st July 2018) - Lu, Hongjian; Qi, Chongchong; Chen, Qiusong; Gan, Deqing; Xue, Zhenlin; Hu, Yajun
Abstract: Waste tailings are increasingly being recycled as cemented paste backfill (CPB) for the cleaner production of mineral resources. In most cases, waste tailings cannot be fully recycled and the stability of underground stopes and open pits cannot be ensured. This research proposed a new procedure for recycling waste tailings as CPB to both underground stopes and open pits. Firstly, the physical, geotechnical and chemical tests required before the application of such procedure were discussed. Then, the new procedure was introduced in detail, including the process parameters determination and the backfill implementation. Finite element method and the three-zone theory were used to determine the process parameters. The application of this new procedure to an engineering instance, the Shirengou Iron Mine (SIM), was expatiated. The process parameters of recycling waste tailings as CPB in SIM were determined as follows. The solids content of CPB was 72%, the cement-tailings ratios were 1:8, 1:10, 1:20, the total height of open pit backfill was 80 m (with four backfilling stages), the stratification height was 1.5 m, and the cement-tailing ratios for four open-pit backfilling stages were 1:8 (stage 1 and 2), 1:10 (stage 3), and 1:20 (stage 4). It is shown that this new procedure achieved 100% recycling of waste tailings in SIM, which is of great environmental significance during mining operations. Harnessing such procedure extends recent efforts to recycle waste tailings as CPB, and can significantly promote the cleaner and safer production of minerals resources worldwide. Graphical abstract: Highlights: A new procedure is proposed to recycle tailings as cemented paste backfill (CPB). Such procedure considers stopes and open pits as a whole system to be backfilled. The required experiments and process parameters are introduced. Its capability is verified at an engineering case, the Shirengou Iron Mine (SIM). The SIM results show that such procedure can achieve 100% recycling of tailings.